(untitled) - International Symposium on the Gerasimov-Drell-Hearn Sum Rule and the Spin Structure of the Nucleon (New Jersey,Singapore, 2003)
This volume contains the proceedings of the GDH 2002 symposium. It is a review of the most recent results on the nucleon spin structure and related sum rules using real and virtual photons. The latest theoretical developments and the new high precision data from different laboratories are presented and discussed. The book provides a comprehensive picture of the nucleon spin studies from the perturbative domain down to the resonance and low momentum transfer region.
Keywords: Nuclear spin,Sum rules (Physics),Scattering (Physics),Spin hạt nhân,Vật được tung rắc